OPEN-ENDED APPROACH TO IMPROVE STUDENTS' MATHEMATICAL COMMUNICATION SKILLS (International Conference on Social and Islamic Studies, 2021)
This study aims to see whether the increase in mathematical communication skills of students who receive learning with an open-ended approach is better than students who receive conventional learning. The population in this study were all UMSU mathematics education students for the 2019/2020 academic year. Sampling using purposive sampling. The research instrument used was a test of students' mathematical communication skills, observation sheets and interview guidelines. Data analysis using T test. The results showed that improving the mathematical communication skills of students who receive learning with an open-ended approach better than students who receive conventional learning. It can be concluded that learning using an open-ended approach can improve students' mathematical communication skills and can increase student activity during learning. Therefore, lecturers and teachers should make learning with an open-ended approach during learning.